Modified Starch of Sorghum Mutant Line Zh-30 for High Fiber Muffin Products - D.D.S. Santosa; S. Human (PPIKSN-BATAN, 2009)
Sorghum mutant line Zh-30 is a breeding line developed at the Center for the Application of Isotope and Radiation Technology, BATAN by using mutation techniques. Gamma irradiation with the dose of 300 Gy was used to induce sorghum genetic variation. Through selection processes in several generations, the mutant line Zh-30 was identified to have better agronomic characteristics, better grain quality and higher grain yield than the original variety. Research on modified starch quality of this mutant line was done to identify its potential use in food industry. Functionality of pregelatinized, hydroxypropyl and crosslinked starch of this mutant line (Mutant TexInstant 30) has been studied for its use in high fiber muffin products. Characteristics of high fiber muffins containing 1.50; 3.50 and 5.50% of Mutant Tex-Instant 30 replacement levels to wheat flour were evaluated using both sensory panel and physical test methods. With regard to the sensory parameters, the high fiber muffins containing 1.50 - 5.50 % Mutant Tex-Instant 30 in general were not significantly different compared to the standard reference muffin. Results of physical evaluations showed that all Mutant Tex-Instant 30 containing products retained more moisture during baking than the standard reference. Tenderness of all products decreased at similar rate following 24 and 48 hr of room temperature storage and seven days at freezer temperature. These results suggested that sorghum mutant line Zh-30 starch could be modified and potentially used in food industry as a subtitute of wheat flour. Received: 26 June 2008; Revised:27 August: 2008; Accepted: 22 December 2008